2018
DOI: 10.1016/j.jbiomech.2018.05.040
|View full text |Cite
|
Sign up to set email alerts
|

Simulated activities of daily living do not replicate functional upper limb movement or reduce movement variability

Abstract: Kinematic assessments of the upper limb during activities of daily living (ADLs) are used as an objective measure of upper limb function. The implementation of ADLs varies between studies; whilst some make use of props and define a functional target, others use simplified tasks to simulate the movements in ADLs. Simulated tasks have been used as an attempt to reduce the large movement variability associated with the upper limb. However, it is not known whether simulated tasks replicate the movements required t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…Conversely, no difference in performance duration was found by Morton et al (1992). The study by Taylor et al (2018) was the only study that evaluated joint range of motion. Greater arcs of shoulder and wrist motion were required to perform functional activities than simulated tasks, for most of the activities evaluated.…”
Section: Quantity Of Motion: Repetitions Duration and Arcs Of Motionmentioning
confidence: 89%
See 2 more Smart Citations
“…Conversely, no difference in performance duration was found by Morton et al (1992). The study by Taylor et al (2018) was the only study that evaluated joint range of motion. Greater arcs of shoulder and wrist motion were required to perform functional activities than simulated tasks, for most of the activities evaluated.…”
Section: Quantity Of Motion: Repetitions Duration and Arcs Of Motionmentioning
confidence: 89%
“…Characteristics of the studies and main results are presented in Table 4. The purposeful activities used in the studies included: personal care (Taylor et al, 2018); writing (Ross & Nelson, 2000;Wu et al, 1994); eating (Hall & Nelson, 1998); using chopsticks (Ma et al, 1999;Rice et al, 2009); reaching for candy (Sackaloo et al, 2015), a mug (Holubar & Rice, 2006;Rice et al, 2009), a bell (Lin et al, 1998;Morton et al, 1992) or a magazine (Rice & Renock, 2006); meal preparation tasks (e.g., slicing vegetables or making cookies) (Fasoli et al, 2002;Hoppe et al, 2008;Miller & Nelson, 1987;Rice et al, 1999;Wu et al, 1998); woodwork or handcrafts (Bakshi et al, 1991); and board or computer games, throwing darts or ping-pong (Kehoe & Rice, 2016;King, 1993;Steinbeck, 1986;Wagner et al, 1995).…”
Section: Purposeful Activities and Motor Performance Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…The maximum and minimum calculated joint angles were recorded for each task type under each experimental condition; the anatomical position and natural posture the participants maintained at the beginning of the experiment were excluded from the calculation. The actual range of motion (ROM) for each experimental condition was defined as the difference between the maximum and minimum joint angle, as described in a previous study (Taylor, 2018). Then, the inter-participant mean and standard deviation (SD) for the maximum, minimum, and actual ROM of each joint angle were calculated for each experimental condition.…”
Section: Measured Data and Analysis 341 Working Posture Measurementmentioning
confidence: 99%
“…The relationship between the movement variability and the anomaly score will be discussed on the basis of the above results. Taylor et al (2018) investigated the movement variability of upper limbs in activities of daily living and reported that the minimum movement variability occurred in the wrist joint angle. However, the movement variability of the elbow flexion angle was smallest when considering the relative value of the range of motion of the joint.…”
Section: Relationship Between the Anomaly Score And Working Posture Variabilitymentioning
confidence: 99%